Association of perceived physical health and physical fitness in two Swedish national samples from 1990 and 2015 - Olsson, S. J. G.; Ekblom‐Bak, E.; Ekblom, B.; Kallings, L. V.; Ekblom, Ö.; Börjesson, M. (Scandinavian journal of medicine & science in sports, 2018)
Perceived health and physical fitness have been shown to correlate, and low levels of either variable increase the risk for future illness and mortality. However, risk factors and their interrelationship may vary between societies and over time. In this study, the associations of physical fitness and perceived health were therefore assessed in two Swedish national samples 25 years apart. Perceived physical health, dichotomized as “good” or “bad,” maximal oxygen uptake (VO2max), counter movement jump (CMJ), balance (one‐legged 60 second stance), and self‐reported demographics and lifestyle were recorded in two cross‐sectional samples (sample size, number of eligible participants) of Swedish adults, aged 20‐65 years, in 1990‐1991 (2203, 1365), and 2013‐2015 (3357, 422). The odds for good perceived physical health increased by 5% per mL·kg−1·min−1 of VO2max, 3% per cm CMJ height, and decreased by 4% per 1 time of overbalancing, in both samples. Mutually adjusted regression models showed that perceived physical health was best predicted by VO2max and chronic illness in 1990 and by age, BMI, and educational level in 2015. Conclusion: Perceived physical health was related to physical fitness in two samples of Swedish adults from 1990 and 2015. However, multivariate and mutually adjusted models indicate that the most important covariates of perceived physical health may have changed from VO2max and chronic illness in 1990, to age, BMI, and educational level in 2015.